Laparoscopic appendectomy for metastatic cervical cancer presenting as appendicitis - Shota Fukai; Alan Kawarai Lefor; Ken Mizokami (Surgical Case Reports)
Abstract Background Metastatic lesions to the appendix are rare. They usually present with acute appendicitis or remain asymptomatic and are diagnosed incidentally. Metastases to the appendix have been reported from a number of primary tumor sites including ovary, colon, gastric and lung. We report a laparoscopic appendectomy for a metachronous metastatic lesion to the appendix from the uterine cervix. Case presentation A 68-year-old woman, who underwent radical hysterectomy for cervical cancer 16 years previously, presented with nausea and gradually worsening right lower quadrant abdominal pain. Abdominal computed tomography scan showed an enlarged appendix and periappendiceal fat stranding. She was diagnosed with appendicitis and underwent laparoscopic appendectomy. Pathological findings showed adenocarcinoma in the submucosa and muscularis propria. Gastrointestinal endoscopy and positron emission tomography with computed tomography (PET–CT) did not show other lesions. Immunohistochemical analysis showed cytokeratin 7 (CK7) positive, cytokeratin 20 (CK20) negative, estrogen receptor (ER) 70–80% and progesterone receptor (PgR) 40–50%. The ER and PgR expression was similar to the cervical lesion 16 years previously, and the diagnosis was a metastatic lesion to the appendix from the uterine cervix. Conclusions Metastasis to the appendix from cancer of the uterine cervix is a rare lesion.